My special one. Volume 8 - Koda, Momoko; Beck, Adrienne (Shojo beat manga., 2024)
"After a mortifying rejection, Sahoko Wakaume has sworn off beautiful boys. But a chance meeting puts her in the sights of gorgeous J-pop star Kouta Kirigaya of the group Like Legend. Sahoko will need all her cynicism to defend herself against Kouta's tenderhearted and affectionate attacks to win her heart! Emika and Kanato have been secretly head over heels for each other for years, but too many misunderstandings have made them unaware of each other’s true feelings. With shooting on their drama wrapping up, Kanato makes up his mind to confess to Emika!"